PENCIPTAAN MANUSIA SEBAGAI REPRESENTATIF ALLAH UNTUK MEWUJUDKAN MANDAT BUDAYA MENURUT KEJADIAN 1:26-28 - Sensius Amon Karlau (Phronesis: Jurnal Teologi dan Misi, 2022)
The understanding of human origins according to philosophical anthropology greatly elevates humans to become equal or even higher than God. On the other hand, there is also a view that tends to reduce the position of humans to be equal like the concept of Homo Sapiens, or lower with other creations which is certainly contrary to the text of the Bible. And ironically, today there are some Christians who are confused about the purpose of God's creation in His Image and Likeness. This study uses a qualitative method with literature study as a data collection technique that is correlated with observation and theological interpretation. Therefore, it is emphasized that humans are creatures created by God in His Image and likeness as men and women who are commensurate with representing themselves as micro theos and microcosms because they are endowed with a unique potential to realize the imperative cultural mandate, namely “to multiply, to multiply. and fill the earth and rule over it according to God's purpose according to Genesis 1:26-28.”